2021
DOI: 10.3390/ijms22168543
|View full text |Cite
|
Sign up to set email alerts
|

Repair Mechanisms of the Neurovascular Unit after Ischemic Stroke with a Focus on VEGF

Abstract: The functional neural circuits are partially repaired after an ischemic stroke in the central nervous system (CNS). In the CNS, neurovascular units, including neurons, endothelial cells, astrocytes, pericytes, microglia, and oligodendrocytes maintain homeostasis; however, these cellular networks are damaged after an ischemic stroke. The present review discusses the repair potential of stem cells (i.e., mesenchymal stem cells, endothelial precursor cells, and neural stem cells) and gaseous molecules (i.e., nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 167 publications
(274 reference statements)
2
41
0
1
Order By: Relevance
“…The HO-1/CO-Nampt-SIRT1 pathway increases vascular endothelial growth factor secretion from astrocytes [ 20 ]. This finding demonstrates facilitated signaling for angiogenesis, neurogenesis, and vascular homeostasis [ 33 , 34 , 35 ]. Taken together, as a putative therapeutic agent, KRGE may enhance neurovascular regeneration after TBI by mediating astrocytic mitochondria activity through HO-1-Tom20.…”
Section: Discussionmentioning
confidence: 99%
“…The HO-1/CO-Nampt-SIRT1 pathway increases vascular endothelial growth factor secretion from astrocytes [ 20 ]. This finding demonstrates facilitated signaling for angiogenesis, neurogenesis, and vascular homeostasis [ 33 , 34 , 35 ]. Taken together, as a putative therapeutic agent, KRGE may enhance neurovascular regeneration after TBI by mediating astrocytic mitochondria activity through HO-1-Tom20.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the transplanted stem cells alter the injured environment via the cytokines secreted. The secreted cytokines might possess the effects of neuroprotection [ 12 , 39 , 40 , 41 ], neuroregeneration [ 42 , 43 ], angiogenesis [ 12 , 41 , 42 , 43 , 44 ], or immunomodulation [ 39 , 45 , 46 , 47 ], and thereby repair the damaged tissues or prevent them from further deterioration. From the RT-PCR results of our study, it is suggested that HUMSCs did not directly differentiate into neurons or astrocytes after transplantation into the infarcted cortex of the chronic stroke rats.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that in rats the systemic administration of MSCs promoted BBB stabilization due to the reduction of BBB leakage and enhancement of microvascular repair [ 65 ]. MSCs transplantation can decrease the expression of IL-1b, IL-6, and TNF-a, and upregulate the tight junction proteins ZO-1 and Claudin-5, thus contributing to the reduction of the BBB permeability in rat stroke model [ 66 ]. Huang et al demonstrated that MSCs induced decline of the tight junction proteins degradation, as well as increased expression of CD31 and pericyte density in the NVU after intravenous administration to rats [ 67 ].…”
Section: Blood–brain Barrier In Stroke and Its Response To Msc Transplantationmentioning
confidence: 99%